Make A Match Model: An Effort to Enhance Problem-Solving and Mathematical Representation Skills - Anggoro, Bambang Sri; Putra, Fredi Ganda; Pupiyanti, Ika (Universitas Islam Negeri Sunan Kudus, 2023)
This study aims to assess the impact of the